Pengaruh Profitabilitas, Likuiditas dan Ukuran Perusahaan terhadap Nilai Perusahaan pada Perusahaan Pertambangan - Abas, Faisal; Damayanti, Damayanti (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
Firm value is the company's performance as reflected by the share price formed by the supply and demand of the capital market. The research conducted aims to examine the effect of profitability, liquidity and company size on firm value in mining companies listed on the Indonesia Stock Exchange (IDX). The population used in the research conducted are mining companies listed on the Indonesia Stock Exchange(IDX) for the 2020-2022 period. Data collection techniques in research conducted using documentation data with the sampling method, namely purposive sampling method. The research samples were thirteen companies for three years, so the number of observations was 36. The data used in the research was secondary data. The data analysis technique used is multiple linear regression analysis techniques. The results showed that profitability had a significant positive effect on firm value, liquidity had an insignificant negative effect on firm value, and similarly company size had a non-significant negative effect on firm value. Keywords: Profabilitas, Likuiditas, Ukuran Perusahaan, Nilai Perusahaan